Dark Letters, Illuminated : Establishing a Catalogue and Initiatory Analysis for the Icelandic Post-Medieval Cryptographic Corpus - Hash, Jason Anthony, 1990- (2017)
Seeking to shed light on the cryptographic tradition within Icelandic history, this thesis is centered around three goals. The first is to establish the presence of alternative alphabets (villuletur), henceforth referred to as ciphers, in Icelandic history from the period of the so-called Viking Age to the 20th century. The emphasis for this being on what can be known regarding the social perceptions of such scripts, as well as the general trends and changes in their usage as well as the general connection and shared history with runes. The second, and largest aim of this thesis is to create and subsequently present the first ever catalogue of formal, organized cipher entries found among what had been defined as the Icelandic Post-Medieval Cryptographic Corpus. Finally, from this catalogue an analysis is performed emphasizing the names and titles applied to the ciphers, with further examination regarding the visual characteristics of the scripts and their degree of overlap and relative variation. This thesis ultimately argues that through cautious analysis of the naming conventions found within the corpus, namely that of ‘rúnir’ and ‘letur’, clues to the origins and influencers of the cryptographic tradition in Iceland can be revealed. Í ritgerðinni er leitast við að varpa ljósi á sögu leynileturs á Íslandi og hverfist hún um þrjá þætti. Í fyrsta lagi er sýnt fram á að villuletur (e. ciphers) var tíðkað allt frá víkingaöld og fram á þá tuttugustu, og áhersla lögð á að hvað hægt sé að vita með vissu um viðhorf fólks til slíkra leturgerða, um notkun þeirra og þróun hennar sem og tengingu við rúnir og sögu þeirra. Í öðru lagi – og það er meginmarkmið ritgerðarinnar – er hér tekin saman og birt fyrsta skráin yfir formleg villuletur sem finna má í því sem höfundur skilgreinir sem heildarsafn íslensks villuleturs frá síðari öldum (The Icelandic Post-Medieval Cryptographic Corpus). Í þriðja lagi eru greind þau nöfn sem villuletrinu í skránni eru gefin og rannsakað hvernig þau tengjast útlitseinkennum letursins og að ...